Pengaruh Pandemi Covid 19 Terhadap Kunjungan dan Penggunaan Obat di Puskesmas Kota Jambi Tahun 2020-2021 - Hisran H; Salmah (Syntax Idea)
In July 2021, Indonesia experienced the peak of COVID-19 cases, with 56,000 reported cases. Simultaneously, the city of Jambi recorded 13,759 cases. To curb the spread of the virus, the government implemented a policy known as Large-Scale Social Restrictions (Pembatasan Sosial Berskala Besar or PSPB). As a result of this policy, there was a 50% decrease in national health visits. There was also a shift in disease patterns towards degenerative conditions such as hypertension, infections, diabetes, and forced labor. The purpose of this research is to provide an overview of the impact of the COVID-19 pandemic on drug prescriptions and visits to health centers in the city of Jambi from 2020 to 2021. The study design employed a descriptive approach with retrospective data collection. Retrospective data were obtained by tracing COVID-19 and health center visit data from documents in the years 2020-2021. Interviews with health center staff were conducted to gather information on drug usage policies and off-site services, as well as specialized drug services during the COVID-19 pandemic. The research findings indicate an increase in cases from 25 in 2020 to 304 in 2021, with the peak occurring in June-July-August 2021. Concurrently, there was an 18.2% decrease in community visits to health centers in 2021, with the highest decline observed from April to August 2021. In 2021, there was an increase in two non-communicable diseases, namely hypertension and diabetes, with a rise of 47.3% for hypertension and 42.5% for diabetes. Statistical analysis revealed a significant correlation of 76.8% with a p-value of 0.05, indicating that there is an impact of COVID-19 cases on the decrease in health center visits. Regarding drug availability, the study found that, on average, health centers had an adequate supply of drugs for over two months based on the end-of-stock inventory.